The Predictive role of speckle-tracking and left ventricular ejection fraction estimation using 2D and 3D echocardiography in the detection of chemotherapy related cardiotoxicity. (14th October 2021) - Oliveira, C C; Coutinho, R; Flores, R; Medeiros, P; Pires, C; Mane, F; Silva, R; Braga, C; Vieira, C; Pereira, V H
Abstract: Background: 2D left ventricular ejection fraction (LVEF) estimation through echocardiography has been the classic parameter for cancer therapy–related cardiac dysfunction (CTrCD) detection. However, it is hypothesized that other parameters can be used in order to detect early stages of subclinical cardiotoxicity when LVEF is still preserved. Therefore, 3D LVEF and 2D and 3D strain parameters assessments have been evaluated in patients submitted to anthracyclines treatment. Objectives: To compare 2D and 3D LVEF and strain parameters estimation using echocardiography regarding its ability to predict and detect subclinical and clinical cardiotoxicity during and after anthracyclines treatment. Search methods and criteria: A systematic review was done and search was performed on PubMed and EMBASE from January 1st of 2000 to October 31th of 2020. Observational studies comparing 2D and 3D echocardiographic exams performed in adult patients submitted to anthracyclines were analyzed. Studies that evaluated survivors of pediatric cancer were excluded. 11 studies were included (n=844 patients). Main results: 2D and 3D LVEF decreased throughout the echocardiographic assessments of 7 studies, but 2D LVEF drops were not statistically significant in 4 studies and 3 studies showed that 3D LVEF detected a superior number of patients with abnormal LVEF. Compared to 3D LVEF, 2D GLS decreased at an earlier point of treatment and detected a superior number of patients with subclinical LV dysfunction. Despite 2D and 3D GLS decreased throughout treatment, 3D GLS measurements were consistently lower and had higher relative variation. All 3D strain parameters decreased during and after the treatment and have higher relative variations than 2D GLS, with the exception of 1 study. 3D GLS reference values are not yet recognized by guidelines, so subclinical LV dysfunction was not evaluated. Conclusions: LVEF estimation through 3D proved to be a better parameter for CTrCD detection vs 2D imaging. GLS is superior to 3D LVEF in detecting earlier LV changes, even if calculated using 2D echocardiography. Moreover, GLS reduction can be a predictor of subsequent LVEF decrease. 3DE is a growing potential technique and may be superior to 2DE in detecting and predicting subclinical LVEF dysfunction and CTrCD, respectively. Though 3D strain parameters presented promising results, more studies are needed to prove its incremental value over 2D strain echocardiography Funding Acknowledgement: Type of funding sources: None.